Análise da evolução do estoque previdenciário dos RPPS estaduais brasileiros - Castro, Maria Ivanilza Fernandes de (2017)
The financial sustainability of the social security system in Brazil has been the subject of many debates in recent years, and the main challenge of the rulers is to maintain the balance of social security accounts. Thus, the objective of this research is to perform a global convergence analysis or a possible formation of convergence clubs between states of the Brazilian federal units using the Phillips and Sul (2007) technique whose results suggest that there is no global convergence of Social Security Own Regimes (SSOR) between the Brazilian states and the Federal District resulting in the formation of six clubs, the first of which is composed of the states of Amapá and Tocantins, the second by the Federal District, Espírito Santo, Maranhão and Paraná, the third by Amazonas, Mato Grosso, Rio de Janeiro and Rio Grande do Norte, the fourth club by Bahia and Mato Grosso do Sul, the fifth by Ceará and Sergipe and the sixth and last club by Alagoas, Paraíba and Santa Catherine. Therefore, the formation of six clubs and ten states that diverge from each other regarding the Social Security Inventory reflects the heterogeneity that exists between the Brazilian federal units, and it is possible that there is a need to implement new government policies that reflect more effective ways to improve in the long term the financial sustainability of the SSOR.